The Sedimentary Context of El Kherba Early Pleistocene Oldowan Site, Algeria: Sediment and Soil Micromorphology Studies - Abdessadok, Salah; Sahnouni, Mohamed; Harichane, Zoheir; Mazouni, Nacim; Chelli Cheheb, Razika; Mouhoubi, Yasmine; Chibane, Saloua; Pérez-González, Alfredo (Frontiers in Earth Science, 2022)
A comprehensive investigation is conducted on the archaeological sediments from the early Pleistocene site of El Kherba (Algeria), involving sediments and soil micromorphology analyses. El Kherba yielded Oldowan stone tools associated with animal fossils from three archaeological levels. The studies aim at assessing the sedimentary processes that acted in the burial of the archaeological remains and at identifying microfacies in order to gain high-resolution paleoenvironmental information pertaining to early hominin behavioral activities at the site 1.8 million years ago. The data indicates that the archaeological assemblages accumulated in sediments with fine grained particles, primarily silt and clay of massive structure, in a floodplain landscape in a temperate climate in the lower part of the stratigraphy and a gradual change from humid to arid environment in the upper part. These results are also supported by taphonomic and isotope studies carried out previously on the site.